FORMY POMOCY UNIJNEJ DLA MAŁYCH GOSPODARSTW ROLNYCH W POLSCE - Stoksik, Jan (Zeszyty Prawnicze, 2016)
Forms of EU Assistance for Small Farms in Poland Summary The latest CAP reform has pointed out the need to maintain the vitality and development of small farms. The basic principle of the reform is for these farms to perform an important role in the multifunctional development of rural areas throughout the whole EU. Alongside their traditional farming activities these farms have a unique favourable impact on the natural environment by maintaining its biodiversity. They also support the rich European traditions and customs in food production. They are producers of good, healthy food; they provide millions of jobs, thereby reducing unemployment, not only in rural areas. In appreciation of these assets, the new EU financial perspective envisages many forms of support, especially financial support for small farms, within both pillars of the CAP. This article gives a favourable preliminary assessment of these forms of assistance. But there are drawbacks as well. One is the small extent of the assistance, expressed by the relatively low amount of expenditure planned for the financing of the assistance. Another drawback is too strict criteria for access to certain forms of financial supports, which could be used by small farms, provided in the Rural Development Programme for the years 2014-2020. This will cause that a large group of small farms do not benefit from the aid provided there.